2013
DOI: 10.1111/eth.12127
|View full text |Cite
|
Sign up to set email alerts
|

Searching for the Audience of the Weeping Lizard's Distress Call

Abstract: The evolution and functions of avian and mammalian antipredator calls are well understood, which contrasts with a lack of progress in reptiles. Here, we present the first investigation of the functions of a distress call in a lizard. We studied Liolaemus chiliensis, which emits a short and complex high‐pitched scream when it is subdued. We determined the behavioral responses of two potential targets to these calls, conspecifics, and a snake predator. Additionally, we tested whether the chemical environment (pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 49 publications
2
29
1
Order By: Relevance
“…From the five behavioral measurements recorded (Table ), only the latency to activity after the stimulus reflected a clear response to distress calls, as was previously reported (Hoare & Labra ). Staying immobile would allow individuals to remain undetected by the predator that is subduing a conspecific in the proximity, which can be particularly relevant for L. chiliensis , which tends to be highly cryptic in scrub branches, and movements may break this crypsis allowing predators to detect the lizards (e.g., Houtman & Dill ).…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…From the five behavioral measurements recorded (Table ), only the latency to activity after the stimulus reflected a clear response to distress calls, as was previously reported (Hoare & Labra ). Staying immobile would allow individuals to remain undetected by the predator that is subduing a conspecific in the proximity, which can be particularly relevant for L. chiliensis , which tends to be highly cryptic in scrub branches, and movements may break this crypsis allowing predators to detect the lizards (e.g., Houtman & Dill ).…”
Section: Discussionsupporting
confidence: 54%
“…Individuals of L. chiliensis respond to conspecific distress calls with prolonged immobility (Hoare & Labra ), a reaction that may reduce their predation risk (e.g., Brodie ; Leal & Rodríguez‐Robles ; O'Keefe et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, predators may be deterred by specific vocalizations, such as distress calls (Toledo, Sazima, & Haddad, ). This defensive signal may surprise and startle the predator (Hoare & Labra, ; Toledo & Haddad, ; Toledo, Sazima, & Haddad, ) during the capture and subjugation phases of predation (Endler, ). Such behaviour may provide sufficient time to allow the prey to escape (Bogert, ; Caro, ).…”
Section: Introductionmentioning
confidence: 99%
“…At first glance, this behavior may seem like a simple expression of pain without a specific adaptive function, but empirical studies across animal taxa have indicated that this behavior may be an adaptive trait that has undergone evolutionary change through natural selection (e.g., Staton 1978;Perrone 1980;Högstedt 1983;GreigSmith 1984;Hödl and Gollmann 1986;Laiolo et al 2004Laiolo et al , 2007Russ et al 2004;Lingle et al 2007a;Blumstein et al 2008;Manno 2012;Hoare and Labra 2013;Løvlie et al 2014;Sepp et al 2014). Several hypotheses that are not mutually exclusive have been proposed to explain the adaptive function of screaming across animal taxa.…”
Section: Introductionmentioning
confidence: 99%